Penerapan Metode role play Dalam Pembelajaran Drama Bahasa Bali di Kelas VIII A SMP N 1 Gianyar - Septarini, Ni Kadek Ragil (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
A teacher should use a learning method that involves students directly. The application of the role play method in learning Balinese drama in class VIII A of SMP N 1 Gianyar is one of the prominent methods in terms of training students' speaking skills and developing students' self-confidence.Based on the explanation above, there are main topics of discussion in the form of problems that will be discussed in this research. The author is interested in researching related to (1) How to use the role play method in learning Balinese drama for class VIII A students at SMP N 1 Gianyar. The theories used to research the problem formulation are: (1) Behaviorism Theory, (2) Constructivism Theory. The research method used is a qualitative research method. Data sources obtained through observation, interviews, documentation and literature. The speakers were the Balinese language teacher for class VIII A, students for class VIII A, and the principal of SMP N 1 Gianyar. The data analysis used is data collection, data reduction, data presentation, drawing conclusions/verification. The results of this research show that the procedures for using the role play method in learning Balinese drama in class VIII A of SMP N 1 Gianyar are divided into 3 stages, namely: (1) Initial activities to make preparations, (2) Core activities for implementing drama using the role method. play the play, (3) Closing reflection and evaluation.Keywords: Role Play Method, Balinese drama learning, SMP N 1 Gianyar